Trust, Care Avoidance, and Care Experiences among Kenyan Women Who Delivered during the COVID-19 Pandemic - Corrina Moucheraud; John Mboya; Doris Njomo; Ginger Golub; Martina Gant; May Sudhinaraset (Taylor & Francis Group, 2022)
ABSTRACTWe explore how the COVID-19 pandemic was associated with avoidance of, and challenges with, antenatal, childbirth and postpartum care among women in Kiambu and Nairobi counties, Kenya; and whether this was associated with a report of declined trust in the health system due to the pandemic. Women who delivered between March and November 2020 were invited to participate in a phone survey about their care experiences (n = 1122 respondents). We explored associations between reduced trust and care avoidance, delays and challenges with healthcare seeking, using logistic regression models adjusted for women's characteristics. Approximately half of respondents said their trust in the health care system had declined due to COVID-19 (52.7%, n = 591). Declined trust was associated with higher likelihood of reporting barriers accessing antenatal care (aOR 1.59 [95% CI 1.24, 2.05]), avoiding care for oneself (aOR 2.26 [95% CI 1.59, 3.22]) and for one's infant (aOR 1.77 [95% CI 1.11, 2.83]), and of feeling unsafe accessing care (aOR 1.52 [95% CI 1.19, 1.93]). Since March 2020, emergency services, routine care and immunizations were avoided most often. Primary reported reasons for avoiding care and challenges accessing care were financial barriers and problems accessing the facility. Declined trust in the health care system due to COVID-19 may have affected health care-seeking for women and their children in Kenya, which could have important implications for their health and well-being. Programs and policies should consider targeted special "catch-up" strategies that include trust-building messages and actions for women who deliver during emergencies like the COVID-19 pandemic.